Efficacy of DNA vaccine encoding koi herpesvirus glycoprotein GP-25in common carp juvenile by immersion - Nuswantoro, Soko; Alimuddin, .; Yuhana, Munti; Santika, Ayi; Nuryati, Sri; Zainun, Zakki; Mawardi, Mira (Jurnal Akuakultur Indonesia, 2012)
Koi herpesvirus (KHV) is a herpesvirus that particularly infects and causes mass mortality to koi and common carp. Therefore, the protection of common carp from KHV infection is urgently needed. In this study, we developed an application of DNA vaccine encoding KHV glycoprotein-25 by immersion method to increase survival of common carp against KHV infection. A total of 400 common carp juveniles at 30-day-old were immersed in 1-L water containing 1.3×108CFU/mL of the killed Escherichia coli cells carrying DNA vaccine. Three frequencies and three duration of fish immersion were tested, namely: 1×30 minutes, 1×60 minutes, 1× 90 minutes, 2×90 minutes and 3×90 minutes by interval of 24 hours. Reversetranscription polymerase chain reaction analysis showed that DNA vaccine was successfully expressed in the vaccinated fish. Fish at twenty eight days post vaccination were challenged by injecting 10-4 mL of KHV per fish. The result showed that vaccination by 1×30 minutes immersion allowed 61% of fish survived, and this was significantly higher (p<0.05) compared to control (without vaccination), but it was similar among vaccination treatments (p>0.05). The relative percent survival of vaccinated fish were also similar among treatments (p>0.05). DNA vaccination has increased fish survival about two fold higher compared to unvaccinated fish control (26.67%). Thus, DNA vaccination was effectively delivered by immersion for 1×30 minutes, and this technique can be useful to level up the resistance of common carp juveniles against KHV infection. Keywords: DNA vaccine, KHV, glycoprotein, immersion, common carp